Visual working memory and sensory processing in autistic children - Ryan A. Stevenson (Nature Portfolio, 2021)
Abstract While atypical sensory processing is one of the more ubiquitous symptoms in autism spectrum disorder, the exact nature of these sensory issues remains unclear, with different studies showing either enhanced or deficient sensory processing. Using a well-established continuous cued-recall task that assesses visual working memory, the current study provides novel evidence reconciling these apparently discrepant findings. Autistic children exhibited perceptual advantages in both likelihood of recall and recall precision relative to their typically-developed peers. When autistic children did make errors, however, they showed a higher probability of erroneously binding a given colour with the incorrect spatial location. These data align with neural-architecture models for feature binding in visual working memory, suggesting that atypical population-level neural noise in the report dimension (colour) and cue dimension (spatial location) may drive both the increase in probability of recall and precision of colour recall as well as the increase in proportion of binding errors when making an error, respectively. These changes are likely to impact core symptomatology associated with autism, as perceptual binding and working memory play significant roles in higher-order tasks, such as communication.